AN EXPLORATORY STUDY ON HOW MALE SECONDARY SCHOOL STUDENTS' ACADEMIC PERFORMANCE CONNECT TO THEIR MATHEMATICS ANXIETY - Onoshakpokaiye, Odiri E. (IJIET (International Journal of Indonesian Education and Teaching), 2024)
Given that it is a required subject in both elementary and postsecondary education, mathematics has been identified by some students as being challenging. Numerous studies have been conducted on various facets of mathematics. However, further research on the psychological characteristics of males in math classes in secondary schools in Delta State is needed, which is why this study was conducted. The study aimed to determine if test anxiety levels among male secondary school students and their academic performance in mathematics are related. Two research questions and two hypotheses were used in the study. The study's design was a correlation. The research population consisted of all 1650 senior secondary year two (SS2) math students in Delta State. A sample of 771 male students was selected using a multistage sampling process. The Mathematics Test Anxiety Questionnaire (MTAQ), which was validated by three experts, was the instrument used to collect data. The reliability coefficient, calculated using Cronbach's alpha, was 0.69. The students’ mathematics scores represent their academic performance. To analyze the data, Pearson product-moment correlation was employed. The study's findings demonstrated that test anxiety levels did not correlate academic performance of male students in secondary school mathematics. Furthermore, there was a sizable gap among male secondary students who had high and low anxiety in math.